"Smart city" concept. Implementation practice. (March 2019) - Vishnivetskaya, Alisa; Alexandrova, Elena
Abstract: Over the past few decades, acceleration of urbanization process in Russia and abroad generated "smart city" concept based on innovative developments integrating into various spheres of urban life. Currently, particular attention is paid to urban environment improvement on the basis of wide information-communication technologies employment. This article is addressing evolution of "smart city" concept and contains analysis of its worldwide implementation in accordance with projects data regarding the degree of their technological and organizational parameters. Results of investigation enabled the authors to reveal obstacles impeding this concept implementation at particular nascent stages, identify factors affecting "smart cities" development, formulate first-priority tasks aiming to eliminate the existing obstacles and propose measures aiming to shape efficient mechanism of "smart cities" development.